CO2-EWR: a cleaner solution for coal chemical industry in China. (15th September 2015) - Li, Qi; Wei, Ya-Ni; Liu, Guizhen; Shi, Hui
Abstract: Anthropogenic greenhouse gas emissions become the primary factor for the global warming, whereas carbon dioxide (CO2 ), as one of the primary greenhouse gases, takes an inescapable responsibility for climate change. Currently, various energy conservation and carbon emission reduction technologies, including the carbon capture and storage (CCS) technology, as well as other clean, low-carbon energy exploitation technologies exhibit a rapid development trend to alleviate the growing crisis of climate change. Other than traditional CO2 geological storage, a novel geoengineering approach of CO2 geological utilization and storage, named CO2 geological storage combining with deep saline water/brine recovery (CO2 -EWR), is put forward to solve the dilemma between the increasing carbon emissions from coal chemical industry and national energy and water security in China. Compared with the traditional CCS technology, CO2 -EWR has two advantages: (1) it can control the relief of reservoir pressure and water production by a reasonable design of pumping wells to achieve the security and stability of the large-scale geological storage of CO2 ; (2) it can collect and process deep saline water after a treatment for life drinking, industrial and/or agricultural utilizations to alleviate the water shortage situation as well as ecological environmental problems, and in addition, the deep brine resources may create considerable profit margins by cascade extraction, which could be used to fill the gap of cost primarily criticized from capture and sequestration processes of current CCS technologies. China mainland can be partitioned into three potential CO2 -EWR zones primarily according to different types of aquifer system, whereas considering research and development maturity and cost prediction of the potential technology adopted, it can be found that coal power and coal chemical enterprises in China's western region have an early opportunity. Three sub-modules of CO2 -EWR technology including CO2 storage in deep saline aquifer, saline water extraction and desalination as well as brine resources utilization are analyzed from a prospective of energy conservation, carbon emission reduction and environmental friendship. Through detailed analyses, it can be concluded that CO2 -EWR technology can be absolutely considered as a clean technology for environmental improvement and green development, and finally development direction and future prospective of the CO2 -EWR technology are pointed out.